2019
DOI: 10.1021/acsami.9b10755
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Aerogels Based on Cyclodextrins: High-Capacity Desiccants Regenerated at Room Temperature by Reducing the Relative Humidity of the Environment

Abstract: Polyurethane aerogels were prepared from a rigid aromatic triisocyanate (tris­(4-isocyanatophenyl)­methane) and cage-shaped α- and β-cyclodextrins as rigid polyols. Gelation was carried out in DMF using dibutyltin dilaurate as catalyst. Wet-gels were dried to aerogels (abbreviated as α- or β-CDPU-xx) with supercritical fluid CO2. “xx” stands for the percent weight of the two monomers in the sol and was varied at two levels for each cyclodextrin: 2.5% and 15%. All aerogels were characterized with solid-state 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 86 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…RESULTS AND DISCUSSION Aerogels were fabricated through a sol−gel process, as detailed in Figure 2a. The Fourier transform infrared (FT-IR) spectra of the final aerogels display the characteristic IR peaks for polyurethane and polyisocyanurate (Figure S3): a broad absorption band in the 3600−3200 cm −1 region assigned to N−H stretching, 42 the urethane and urea carbonyl stretching absorptions at 1709 and 1597 cm −1 , respectively, the N−H bending coupled to the C−N stretching is detected at ca. 1513 cm −1 , the isocyanurate carbon−nitrogen stretching is present at 1412 cm −1 , 43 and the C−N stretch can be observed at ca.…”
Section: Methodsmentioning
confidence: 99%
“…RESULTS AND DISCUSSION Aerogels were fabricated through a sol−gel process, as detailed in Figure 2a. The Fourier transform infrared (FT-IR) spectra of the final aerogels display the characteristic IR peaks for polyurethane and polyisocyanurate (Figure S3): a broad absorption band in the 3600−3200 cm −1 region assigned to N−H stretching, 42 the urethane and urea carbonyl stretching absorptions at 1709 and 1597 cm −1 , respectively, the N−H bending coupled to the C−N stretching is detected at ca. 1513 cm −1 , the isocyanurate carbon−nitrogen stretching is present at 1412 cm −1 , 43 and the C−N stretch can be observed at ca.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Parwani and colleagues developed polyurethane aerogels by combination of cyclodextrins as rigid polyols and a rigid aromatic triisocyanate. [ 214 ] During the gelation process, dibutyltin dilaurate was chosen as a catalyst and tested under the condition of room temperature. They concluded that the samples exhibited stronger abilities in moisture sorption from humid environments (RH level 99%) than traditional desiccants.…”
Section: Polymer Materials In Sdc Systemmentioning
confidence: 99%
“…Solid desiccants , may be preferred over liquid desiccants since they are non-corrosive, have lower maintenance costs, larger surface area, and offer flexible applications . Silica has been employed for drying in many applications .…”
Section: Introductionmentioning
confidence: 99%